New space-times. Immersivity in the digital age (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2022)
The concept of immersiveness is no longer specific, but instead embodies a complexity that is linked to the context of real-digital mystification. The polyhedral nature of this new conception of immersiveness makes necessary to resignify this concept and its scope in our daily lives. Through the spectator, screen and virtual reality elements, we reflect on the different facets of immersion and itsdegrees of depth today.
Keywords: Immersiveness; viewer; screen; virtual reality; digital universe